White Dwarfs in Cataclysmic Variables: An Update - E. M. Sion; P. Godon (Acta Polytechnica CTU Proceedings)
In this review, we summarize what is currently known about the surface temperatures of accreting white dwarfs in nonmagnetic and magnetic cataclysmic variables (CVs) based upon synthetic spectral analyses of far ultraviolet data. We focus only on white dwarf surface temperatures, since in the area of chemical abundances, rotation rates, WD masses and accretion rates, relatively little has changed since our last review, pending the results of a large HST GO program involving 48 CVs of different CV types. The surface temperature of the white dwarf in SS Cygni is re-examined in the light of its revised distance. We also discuss new HST spectra of the recurrent nova T Pyxidis as it transitioned into quiescence following its April 2011 nova outburst.